3y-3(6)+2x=

Simple and best practice solution for 3y-3(6)+2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-3(6)+2x= equation:


Simplifying
3y + -3(6) + 2x = 0

Multiply -3 * 6
3y + -18 + 2x = 0

Reorder the terms:
-18 + 2x + 3y = 0

Solving
-18 + 2x + 3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 2x + 18 + 3y = 0 + 18

Reorder the terms:
-18 + 18 + 2x + 3y = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 2x + 3y = 0 + 18
2x + 3y = 0 + 18

Combine like terms: 0 + 18 = 18
2x + 3y = 18

Add '-3y' to each side of the equation.
2x + 3y + -3y = 18 + -3y

Combine like terms: 3y + -3y = 0
2x + 0 = 18 + -3y
2x = 18 + -3y

Divide each side by '2'.
x = 9 + -1.5y

Simplifying
x = 9 + -1.5y

See similar equations:

| 2x+30=5x-30 | | 12.5=y | | T+10-4r=-11 | | 3k+15+2x=5(x+5) | | 4x^2+y^2-3x+16y+124=0 | | .25x+.5y=7.75 | | 7*5+0.5*5= | | (3)3x=2x+20 | | Y=2x^3-4x^2+8 | | 5+21=x+13 | | 170-w=248 | | (9x-1)(5x+3)=0 | | 3x+11-6x-21=2 | | 3(6x-5)=6(x+4)-3 | | 5(-8x+12)= | | x^2+100=x^2+16 | | 4y=19+-7x | | (4)x=20 | | 2y-12=8 | | 0.95X+0.05(10-x)=0.10(-31) | | 2wp=p | | -7x^2-55x-42= | | 7x-4y=19fory | | 3-3a=12 | | X^3-12X^2+4X-30= | | 2w+13=49 | | 2wy=p | | 4.9x^2=-5 | | 2(x-1)+3x=-2 | | 5x-9x=44-16 | | 4x+160y=136 | | 5x-9=44-16 |

Equations solver categories